2018
DOI: 10.1017/s0954102018000135
|View full text |Cite
|
Sign up to set email alerts
|

Population trends of seabirds at Stinker Point, Elephant Island, Maritime Antarctica

Abstract: Available information about seabird breeding population trends on Stinker Point (Elephant Island, Maritime Antarctic Peninsula) is outdated by decades. This study reports current numbers of breeding species, and evaluates population trends over 28 years. We counted breeding pairs of seabirds along all ice-free areas on Stinker Point during two distinct periods (summers of 1985/86–1991/92 and 2009/10–2013/14). Thirteen species currently breed in the area: four Sphenisciformes, four Procellariiformes, one Sulifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…Much of the census data from the Antarctic Peninsula and South Shetland Islands are collected via opportunistic vessel-based field surveys (Lynch et al 2013), though several additional surveys near permanent stations have been published (Petry et al 2018;Smagol et al 2018;Dunn et al 2019). Most surveys were conducted via manual ground counts of individual nests, counting individual nests in panoramic photos taken from the ground or from an offshore vessel, or counting individual penguins from aerial photographs captured by unmanned aerial vehicles (Borowicz et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the census data from the Antarctic Peninsula and South Shetland Islands are collected via opportunistic vessel-based field surveys (Lynch et al 2013), though several additional surveys near permanent stations have been published (Petry et al 2018;Smagol et al 2018;Dunn et al 2019). Most surveys were conducted via manual ground counts of individual nests, counting individual nests in panoramic photos taken from the ground or from an offshore vessel, or counting individual penguins from aerial photographs captured by unmanned aerial vehicles (Borowicz et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Since the last global assessment of approximately 387,000 breeding pairs (Lynch 2013), many new data have been collected across the Gentoo Penguin's distributional range. While the WAP population has been generally increasing, these trends are not homogenous, as some colonies have experienced recent declines (Petry et al 2018;Dunn et al 2019). In addition, the population in the Falkland Islands, where approximately one third of all Gentoo Penguins nest, increased overall by 105% between 2005 and 2010 (Baylis et al 2013), though a subset of annually monitored colonies have since declined (Crofts and Stanworth 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Petry et al (2016) reported both an increase of breeding pairs as well as the disappearance of some smaller breeding colonies between 1979 and 2011 in Admiralty Bay in the period. However, Petry et al (2018) reported a considerable decline from approximately 1500 breeding pairs in 1988 to approximately 600 breeding pairs in 2014 for Elephant Island. Published data on breeding success are even scarcer.…”
Section: Discussionmentioning
confidence: 99%
“…Arnould and Whitehead 1991;Weidinger 1996aWeidinger , 1997Weidinger , 1998bCoria et al 1997) there are few surveys of their abundance (e.g. Coria et al 1995Coria et al , 1996Woehler and Croxall 1997;Bó and Copello 2000;Lumpe and Weidinger 2000;Soave et al 2000b;Sierakowski et al 2017;Petry et al 2018), but these mostly do not allow any assessment of population trends. This is mainly due to cape petrel breeding habits as the birds nest on rock ledges and cliffs along the coastline and this usually hinders accurate counting.…”
Section: Introductionmentioning
confidence: 99%
“…The survey revealed the diversity of the vegetation cover reporting over 37 species of plants (the two native phanerogams Deschampsia antarctica and Colobanthus quitensis and 35 bryophytes) and 54 species of lichens (Pereira & Putzke 1994). The fauna is represented by a large number of marine mammals (weddell seals, antarctic fur seals, southern elephant seals); large colonies of penguins (Pygoscelis papua and P. antarcticus) and numerous nests of giant southern petrels (Macronectes giganteus), skuas (Stercorarius antarcticus) and other birds (Petry et al 2018).…”
Section: Introductionmentioning
confidence: 99%